EKSISTENSI KOMISI YUDISAL DALAM STRUKTUR KETATANEGARAAN REPUBLIK INDONESIA DAN YANG SEHARUSNYA DIATUR DALAM PERATURAN PERUNDANG-UNDANGAN - Fauzan, Muhammad (Jurnal Dinamika Hukum, 2008)
Existence of Judicial Commission in system of Republic of Indonesia is a long process in searching format of civic specially related to execution of judicial power. The chaos of execution of judicial power which influence of government and other power's have pushed  the importance of a institute that able to " guarantee" the judicial power in order to according with the justice . the judicial Commission althought arranged in Chapter of IX UUD 1945 concerning Judicial Power, but judicial  Commission is not executor of judicial power, Therefore Judicial Commission is not as institute enforcer of law of code, but as institute enforcer of ethic norm (ethics of code). Judicial Commission is expected can support the creation execution of judicial power which independence and free from other power. Kata Kunci : Komisi Yudisial, Struktur Ketatanegaraan, Peraturan Perundang-undangan